Kualitas Pelayanan Antenatal Bidan Dan Pencapaian Cakupan K4 Bidan Desa Di Kabupaten Rembang - Indrawati, Fitri (STIKES Wira Husada Yogyakarta, 2015)
ABSTRACT Many factors affect the achievement of K4. Coverage of K4 in Rembang District in 2013 has yet to reach the target set by the national (93%) that is equal to 80,79%. The purpose of this study was to determine the relationship between the quality of antenatal care provided by midwives with the coverage K4 midwife. The study is an observational analytic study with cross sectional approach. The population in this study were all midwives in Rembang, amounting to 287 midwives. The sample in this study is the 75 village midwive. The results of this study showed that there was significant relationship between the quality of antenatal care provided by midwives with the coverage K4 midwive.